Integrasi Kecerdasan Buatan dalam Perencanaan Pembelajaran Pendidikan Agama Islam (PAI): Studi Fenomenologis tentang Pengalaman Guru - Febriyanti Febriyanti; Leny Marlina; Winda Andini; Masariel (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the Integration of Artificial Intelligence in Islamic Religious Education Learning Planning: A Phenomenological Study of Teachers’ Experiences. The study employed a phenomenological qualitative approach to explore the experiences of Islamic Religious Education (PAI) teachers in facing the digital transformation of the Society 5.0 era. Using the Interpretative Phenomenological Analysis (IPA) method, the research examined teachers’ perceptions, beliefs, and subjective experiences. Data were collected through interviews, observations, and documentation involving 12–15 purposively selected teachers. The analysis followed IPA procedures, while data trustworthiness was ensured through the criteria of credibility, transferability, dependability, and confirmability. The analysis results indicate that the readiness of Islamic Education (PAI) teachers is understood as a multidimensional construct encompassing technological competence, pedagogical transformation, ethical awareness, and institutional support. The integration of technology, especially AI, in learning is not only technical but rooted in Islamic values and strengthens the human role in the era of Society 5.0. This study has limitations in terms of the relatively small number of participants and context-specific focus on certain madrasahs, so the findings cannot yet be generalized widely. Future research is recommended to expand the locations, involve mixed methods approaches, and examine the effectiveness of AI implementation on learning quality and character development of students.